Use of Local Building Materials in the Natural Climate of Central Asia (Texas Journal of Engineering and Technology, 2022)
This article discusses the use of raw brick in the construction of Uzbekistan since ancient times in connection with climatic conditions, as well as the process of preparing and using local building materials used in the repair of patterns and decorations of architectural monuments.